Modeling effective multimedia technology based learning for management undergraduates - P. Rajandran, Peresamy (2010)
The management undergraduate students' are from different demographic backgrounds and have different learning style preferences. These students are exposed to multimedia technology based learning environment during their undergraduate studies. The consideration and incorporation of demographic factors, learning styles and the use of multimedia technology in the learning process are necessary for effective learning. The objectives of this research are to identify the learning style preferences of management undergraduates in Malaysia, to assess the relationship between the demographic factors and learning styles, to measure the role of learning styles on effective learning, to assess the effects of multimedia technology on effective learning, and based on the above findings to develop an effective learning model for management undergraduates. This effective learning model is developed by incorporating the students' demographic factors, their learning styles and multimedia technology. This model is also intended to propose an appropriate use of multimedia technology to achieve effective learning for management undergraduates. The findings of this research are based on students' perceptions of the above research problem. According to Honey & Mumford (1992), learning style is a group of attributes and behaviors that determine an individual learner's preference in learning. This is also in accordance to the 'Experiential Learning Style Model' by Felder (1988) which identifies 8 types of learning styles i.e. active, reflective, sensing, intuitive, visual, verbal, sequential and global. According to Imran (2009) multimedia technology has affected the overall education strategies which have influenced the learning environment. The multimedia technology affects the learning styles of students. In this exploratory research the questions on the independent variables (learning styles) are adopted from the Index Learning style (ILS) developed by Felder-Soloman (1991 ). The moderator variable (multimedia technology) and the dependent variable (effective learning) are also incorporated in the research. Results of the research assist to identify the learning style preferences of management undergraduates, the relationships between the demographic factors and learning styles, and the learning styles influences on effective learning. Some selected multimedia technology related aspects have been tested with the learning styles to identify the effects of these variables on effective learning. The quantitative research survey method using questionnaire was used to collect seven hundred and three samples and the analysis was done with SPSS version 16. Based on the mean scores, the study shows that the dominant learning style in sequence are visual, sequential, reflective, sensing, global, active, intuitive and verbal. In the relationship of demographic factors to learning styles, the male students are found dominant in active, intuitive and global learning styles compared to the female students. In terms of ethnicity, the mean score for active, intuitive and global are more significant for at least one pair of ethnic group. There are significant mean score differences for STPM, diploma and matriculation students in active and sensing learning styles. In the education domain, the mean score for marketing students is higher compared to finance/banking students in sensory learning. The average score of students in public higher learning institutions is more significant compared to the private higher learning institutions in active, intuitive, visual, verbal and global learning styles. In the year of study there are significant differences in the means for sensing, visual, verbal and global learning styles for at least one pair of year of study. The data analysis results show the influences of gender, ethnicity, entry qualifications, field of study, type of learning institution, and year of study on learning styles. The learning styles, that influence the effective learning of management undergraduates, were tested and the results show that there are 6 effective learning styles: active, reflective, visual, verbal, sequential and global. The multimedia technology related aspects, assessed in this research, are multimedia technology based education system, multiple views created for clarity using multimedia technology, multimedia technology's support to meet learners' learning needs and consistently placed navigational elements in multimedia technology for effective learning. The analysis conducted shows that each multimedia technology aspect and the overall multimedia technology as a moderator have effects on the six learning styles of the students. In summary, this research has identified the management undergraduates' learning style preferences, their relationship with demographic factors, the influences of learning styles on effective learning and the effects of multimedia technology on learning. The contribution of this research is the development of an effective learning model that incorporates demographic factors, learning styles and the use of multimedia technology in the creation of an effective learning environment for management undergraduates.